Evaluating the effect of drying methods on the properties of a water base drilling mud (2021)
It is important to understand the properties influencing the efficiency of a drilling fluid while drilling for oil and gas. As a result, drilling fluid must be designed in order to comply with three important requirements which are easy to use, cost effective and being environmentally friendly. Several studies have been carried out on the use of local materials as suitable substitute for imported additives. This study focuses on the use of starch processed from local cassava (Manihot esculenta Crant), (TME 419) using the process of wet milling and dried using three different methods namely: oven drying, direct heating and sun drying Due to this short coming resulting from the use of native starch, the starch was chemically modified using the process of esterification before being used as additive for treatment of the water-based drilling. The mud samples were prepared using Wyoming bentonite and distil water as the base fluid. Varying concentration of additives (0.5, 1.0 and 1.5 g) were added to the different mud samples and the laboratory test carried out in accordance with the API Recommended Practice 13B at varying temperatures (30, 50.70 and 90°C). The various mud samples rheological properties was determined using a Fann35A rheometer and the filtration properties using a low –Temperature and High –Pressure API Filter Press at 100 psi with a 3.5” filter paper. The mud samples labelled labeled A, B and C were treated with oven dry, direct heat and sundry modified starches, respectively. While two control mud samples were prepared using low viscous Carboxymethyl cellulose for mud sample D and extra high viscous CMC in sample E. Although the Viscosity and fluid loss profiles result of the mud samples comparable performance with that of the commercial CMC’s. However, mud samples treated with oven dried starches presented the best results in their rheological as well as fluid loss properties.